Familial hypocalciuric hypercalcaemia type 3: AP2S1 missense mutation - Kerut, Sarah (BMJ Case Rep, 2020)
A 45-year-old man was referred to endocrine for the evaluation of hypercalcaemia. The calcium was elevated, vitamin D was low with a normal parathyroid hormone. Dual-energy X-ray absorptiometry scan revealed osteoporosis at the lumbar spine and femoral neck. A 24-hour urine collection revealed low urinary calcium, which was believed to be secondary to vitamin D deficiency. A diagnosis of primary hyperparathyroidism was made. The patient underwent a four-gland parathyroid exploration surgery in which three of his parathyroid glands were removed. The pathology was consistent with benign parathyroid tissue. Post surgery, the patient had persistently elevated calcium levels. He was then started on bisphosphonate and cinacalcet for osteoporosis and hypercalcaemia, respectively. Genetic analysis of familial hypocalciuric hypercalcaemia (FHH) showed a p.arg15cys mutation in the AP2S1 gene, confirming the diagnosis of FHH type 3.